Restoration of natural disturbances: impact on distribution and performance of dominant ants (Formica spp.) by fire and gap dynamics - Larsson, Rebecca (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2015)
Disturbance regimes caused by fire and wind storms used to be common features in the Swedish boreal forests. However, due to an intense forest management, these events have declined rapidly. Little is known about how natural disturbances affect mound-building ants, even though they are important for ecological processes in their role as ecosystem engineers. Effects on ant communities could thus result in further effects on many other species. Wood ants (Formica spp.), a sub-group to mound-building ants, have due to their aggressive behavior and large distribution become the dominant ant species in Swedish forests. The aim of this study was to investigate how restoration of natural disturbances affects the distribution and performance of mound-building ants. Field inventories were conducted during June 2015 in stands subjected to burning and gap creation, with untreated stands used as references. Differences in nest density, ant activity and harvesting of honeydew were measured in the different stand types. My results showed a direct negative affect of fire on nest volume, whilst no effect was found as a result of gap creation. Furthermore, no differences in ant activity among stand types were found, nor did the harvesting rate of honeydew differ. Due to the cold weather for the season, ant activity was in general low, hence resulting in a low honeydew load. My results suggest that ant performance is not affected by the restoration treatments in the short term, but the lack of differences between burned and reference stands might be a result of an adjustment to available resources of the ants. Additionally, the reduced nest volume within burned stands can have further effects on other species interacting with ants. The whole picture of overall effects require a long-term study, and I suggest continued monitoring of Formica spp. ant communities over time.